Performance Models for Frost Prediction in Public Cloud Infrastructures - Iacono, Lucas E.; Vázquez Poletti, José Luis; García Garino, Carlos; Llorente, Ignacio Martín (Computing and Informatics, 2018)
Sensor Clouds have opened new opportunities for agricultural monitoring. These infrastructures use Wireless Sensor Networks (WSNs) to collect data on-field and Cloud Computing services to store and process them. Among other applications of Sensor Clouds, frost prevention is of special interest among grapevine producers in the Province of Mendoza - Argentina, since frost is one of the main causes of economic loss in the province. Currently, there is a wide offer of public cloud services that can be used in order to process data collected by Sensor Clouds. Therefore, there is a need for tools to determine which instance is the most appropriate in terms of execution time and economic costs for running frost prediction applications in an isolated or cluster way. In this paper, we develop models to estimate the performance of different Amazon EC2 instances for processing frosts prediction applications. Finally, we obtain results that show which is the best instance for processing these applications.